Crystallization properties of arsenic doped GST alloys - Vinod E. Madhavan (8136774) (2019)
We present the enhanced properties observed in the phase change memory alloy Ge2Sb2Te5 (GST) when doped with arsenic. Although arsenic is known as a toxic element, our observations show that significant improvement can be obtained in GST systems on thermal stability, transition temperature between amorphous and crystalline phases and switching behaviors when doping with arsenic. Though both the GST and arsenic doped GST are amorphous in the as-deposited state, only GST alloy turns to crystalline NaCl-type structure after annealing at 150 °C for 1 h. Results from the resistance versus temperature study show a systematic increase in the transition temperature and resistivity in the amorphous and crystalline states when the arsenic percentage in the GST alloy increases. The crystallization temperature (Tc) of (GST)0.85As0.15 is higher than the Tc observed in GST. Optical band gap (Eopt) values of the as-deposited films show a clear increasing trend; 0.6 eV for GST to 0.76 eV for (GST)0.85As0.15. The decreases in Eopt for the samples annealed at higher temperatures shows significant optical contrast between the as-deposited and annealed samples. Though all (GST)1−xAsx alloys show memory switching behaviors, threshold switching voltages (VT) of the studied alloys show an increasing trend with arsenic doping. For (GST)0.85As0.15, VT is about 5.2 V, which is higher than GST (4.0 V). Higher transition temperature and higher threshold switching values show arsenic doping in GST can enhance the memory device properties by improving the thermal stability and data readability. Understanding the doping effect on the GST is important to understand its crystallization properties. Structure properties of amorphous GST, Ge2Sb2−0.3As0.3Te5 and (GST)0.85As0.15 models were studied using first principles molecular dynamics simulations, compared their partial radial distribution functions, and q parameter order. Arsenic doping into GST features interesting structural and electronic effects revealed by the radial distribution functions, q order parameter and band gap value, in line with the experimental findings. Other Information Published in: Scientific Reports License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1038/s41598-019-49168-z